Síntese de porfirinas contendo grupos do tipo uracil fundidos nas posições β-pirrólicas - Fujita, Marta Akemi (Universidade Federal de São Carlos, 2014)
In this work the synthesis of new porphyrin derivatives were proposed. The preparations of new compounds containing uracil groups at β-pirrolic position were studied based on their interest in organics synthesis. We also have performed reactions with metals salt in order to evaluate the different photophysical properties of the porphyrin complex. In the first step was performed the synthesis of precursors 2, 3 and 4 in order to prepare porphyrins 5 and 6 (SCHEME 1). The pyrrole 3 was obtained from the protected uracil 2. For the synthesis of the pyrrole 4, a deprotection was performed before, to yield the compound 3. After the synthesis both 3 and 4, tetramerization reactions were tested under acid conditions, to yield porphyrins 5 and 6 after aromatization. Classic conditions for the porphyrin synthesis were tested aiming at the obtainment of porphyrinoids in good yields, thus a systematic study was performed. Until this part, only the porphyrin 5a was obtained. And the synthesis of the compound 5a, we have observed a regioisomer mixture through the 1H NMR. It was expected since pyrrole 3 was not symmetric. (CONTINUE.......)
Synthesis of porphyrin containing β-fused uracil groups
Keywords: Síntese orgânica; Porfirina; Terapia fotodinâmica; Metaloporfirinas; Uracil; CIENCIAS EXATAS E DA TERRA::QUIMICA